Impact Analysis of Economic Linkages of South Korea with North Korea Using a CGE Model - Euijune Kim; Hyewon Shin (European Regional Science Association (ERSA), 2014)
The purpose of this paper is to estimate impacts of core infrastructure investments in North Korea on South and North Koreas. The investment expenditures of core infrastructure projects in North Korea are calibrated as 9.35 billion US including highway, railroad and industrial complex. Since South and North Koreas are based on market and planned economies respectively, the Computable General Equilibrium model is applied to the economic analysis of South Korea and an Input-Output Model for that of North Korea. The base year for the analysis is year of 2007 due to the data availability of North Korea. The CGE model for Korean economy accounts for the economic behavior of producers and consumers on the real side economy, following the neoclassical elasticity approach such as market-clearing prices, the maximization of a firm's profit, and a household's utility. This paper finds that the annual total output of North Korea would increase by 20.30 billion US with investments on infrastructure projects. This could result in increases of GDP of Korea by 2.16 billion US as a construction effect and by 0.08 billion US as an operation effect on the annual average.
Keywords: R13; 330; CGE Model; Regional Economies; Economic Impact